OmpA, a Common Virulence Factor, Is Under RNA Thermometer Control in Yersinia pseudotuberculosis - Scheller, Daniel; Twittenhoff, Christian; Becker, Franziska; Holler, Marcel; Narberhaus, Franz (Frontiers in Microbiology, 2021)
The outer membrane protein OmpA is a virulence factor in many mammalian pathogens. In previous global RNA structure probing studies, we found evidence for a temperature-modulated RNA structure in the 5’-untranslated region (5’-UTR) of the Yersinia pseudotuberculosis ompA transcript suggesting that opening of the structure at host-body temperature might relieve translational repression. Here, we support this hypothesis by quantitative reverse transcription PCR (qRT-PCR), translational reporter gene fusions, enzymatic RNA structure probing and toeprinting assays. While ompA transcript levels decreased at 37°C compared to 25°C, translation of the transcript increased with increasing temperature. Biochemical experiments show that this is due to melting of the RNA structure, which permits ribosome binding to the 5’-UTR. A point mutation that locks the RNA structure in a closed conformation prevents translation by impairing ribosome access. Our findings add another common virulence factor to the growing list of pathogen-associated genes that are under RNA thermometer control.